Leadership: Leadership and Coaching was given to Young Teacher participants - Djoko Soelistya (International Journal of Educational Research Excellence (IJERE), 2024)
After leadership training has been carried out, Young Teachers will have and demonstrate leadership behavior skills that are ready to take on challenges and can inspire students and other parties. From the training activities carried out, it can be concluded that the extension participants felt happy and satisfied with the exposure given. This is because the participants gain new understanding and skills in demonstrating leadership behavior. Indonesia Mengajar is a movement whose main activity is recruiting, training and sending young Indonesians who are the best university graduates, to serve for one year in various regions in Indonesia as elementary school teachers. Apart from their basic duties as teachers, these Young Teachers have the mandate to drive behavioral change in their places of duty.